The core of the global corporate network - Ricardo Giglio; Thomas Lux (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We investigate the network topology of a comprehensive data set of the world-wide population of corporate entities. In particular, we have extracted information on the boards of all companies listed in Bloomberg's archive of company profiles in October, 2015, a total of almost 100; 000 firms. We provide information on board membership overlap at various levels, and, in particular, show that there exists a core of directors who accumulate a large number of seats and are highly connected among themselves both at the level of national networks and at the worldwide aggregated level.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: D85; L20; M14; M51; 330; board and director interlocks; network core; network formation